Agency at/of the waterfront in New York City: Vision 2020 and New York 2140 - Lieven Ameel (My University, 2022)
From literary fiction to planning and policy visions, narratives frame, question, and shape the future and our possibilities to act upon it. This paper approaches the question of narrated agency in future narratives through the lens of the New York waterfront, explored here as a site for enacting and critiquing the possibility to act towards the future. Who is described as having the possibility to act at the waterfront, and to what extent is the water seen as a force in its own right? This essay addresses these questions by examining two key texts imagining a future New York City: the New York Comprehensive Waterfront Plan Vision 2020 (2011) and Kim Stanley Robinson’s New York 2140 (2017). It argues that both texts gesture towards an acknowledgement of possible agency of the water, while continuing to reiterate an instrumental relationship with the environment that focuses on processes of appropriation, distribution and production. Ultimately, this essay considers the implications for the implied readers’ agency, and for their possibilities to take meaningful action to interact with, and make changes in, their relationship with the water.